Subjects With Unilateral Neovascular AMD Have Bilateral Delays in Rod-Mediated Phototransduction Activation Kinetics and in Dark Adaptation Recovery - Dimopoulos, Ioannis S.; Tennant, Matthew; Johnson, Antonia; Fisher, Stacey; Freund, Paul R.; Sauvé, Yves (Investigative ophthalmology & visual science, 2013)
To assess the impact of early (dry) and late (wet/neovascular and/or atrophic) forms of AMD on panretinal function. Light- and dark-adapted full-field ERG recordings were obtained over a 5-log-unit intensity range from both eyes of 25 patients with unilateral wet AMD. Fellow eyes showed various signs of dry AMD ranging from multiple medium-sized drusen to noncentral geographic atrophy. The leading edges of rod-isolated ERG a-waves were fitted to a quantitative model of phototransduction. ERG a- and b-wave amplitudes and implicit times were compared between wet and dry AMD eyes and from non-AMD eyes of age-matched subjects. A quantitative and objective assessment of dark adaptation was achieved by recording the recovery of the pure rod b-wave (postsynaptic depolarization of rod bipolar cells); b-wave amplitudes were measured at 120-second intervals for 20 minutes and normalized to the amplitude recorded at t = 20 minutes. Delays in mixed a- and b-wave implicit times were recorded in both wet and dry AMD eyes. Time required to reach 50% of fully recovered responses was delayed in all wet and dry AMD eyes independently of dry AMD severity in the fellow eye. Generalized cone dysfunction and slower activation of the rod phototransduction cascade was noted in a subgroup of patients with advanced features of dry AMD in the fellow eye. Patients with unilateral wet AMD display rod dysfunction in both their wet and dry AMD eyes. A subset of these patients display, in addition, bilateral cone dysfunction and delayed rod phototransduction activation, which may either reflect extensive morphologic change in advanced stages of AMD and/or represent a distinct phenotypic manifestation within the heterogeneous context of AMD as a disease.